2019
DOI: 10.3390/jcm9010028
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Gait Deviation Index and Physical Function in Children with Bilateral Spastic Cerebral Palsy: A Cross-Sectional Study

Abstract: This study examined the association between Gait Deviation Index (GDI) and the five-times-sit-to-stand test (FTSST) or gait speed results, which represent mobility and muscle strength of the lower extremities in ambulatory children with Gross Motor Function Classification System (GMFCS) level I and II spastic cerebral palsy. In this cross-sectional, observational study, three-dimensional gait analysis data were obtained during gait trials to evaluate the GDI in 35 children (age 5-16 years) with spastic palsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
12
0
3
Order By: Relevance
“…Malt et al and Maanum et al report identical mean GDI values for GMFCS levels I and II [26,40]. Additionally, though evaluating patients with bilateral CP, Ito et al described the same mean values for the different GMFCS levels as found during our investigation [41]. It seems, that the GDI might reflect GMFCS levels independently from the underlying neurological disorder.…”
Section: Discussionsupporting
confidence: 76%
“…Malt et al and Maanum et al report identical mean GDI values for GMFCS levels I and II [26,40]. Additionally, though evaluating patients with bilateral CP, Ito et al described the same mean values for the different GMFCS levels as found during our investigation [41]. It seems, that the GDI might reflect GMFCS levels independently from the underlying neurological disorder.…”
Section: Discussionsupporting
confidence: 76%
“…Alternation of GDI, a new multi-variate measure of overall gait performance obtained from walking strides to derive a set of mutually independent joint rotation patterns that e ciently describe gait pathology (ranging from 0 to 100. GDI of 100 means that there is no gait pathology) was also used to assess the gait pattern changes in our cases after SDR [16][17][18][19][20][21] . Results showed general improvements of GDI in those affected sides, resulting into GDI elevation in both sides at the last time of GA assessment after a mean duration of 9.9 months post-SDR rehabilitation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(2) In the second stage, we adopted the idea suggested by Schwartz [ 66 ], which find many applications in the literature [ 67 , 68 , 72 , 73 ]. It consists of multiplying a ratio by 10 and subtract them from 100 to give at each stride a gait deviation index we labeled (Equation (7)): where is the suggested risk of falling (ROFA) score according to the gait parameter .…”
Section: Methodsmentioning
confidence: 99%